Percutaneous decannulation of venoarterial extracorporeal membrane oxygenation using the Manta vascular closure device: A systematic review and meta‐analysis - Ng, Jun Jie; Lee, Stefanie H. T.; Lim, Joseph K. W.; Chan, Karen K. W.; Lim, Mark D. S.; Ahmed, Mohamed A. I.; Loh, Stanley E. K.; Choong, Andrew M. T. L. (Artificial organs, 2023)
To perform a systematic review and meta-analysis of the techniques and outcomes associated with percutaneous decannulation of venoarterial extracorporeal membrane oxygenation (VA-ECMO) using the Manta vascular closure device. Peripheral VA-ECMO can be used to treat critically ill patients with conditions such as refractory cardiogenic shock. After percutaneous implantation of VA-ECMO, VA-ECMO can also be decannulated completely percutaneously by using a vascular closure device. The Manta vascular closure device is a dedicated device used in the closure of large-bore arteriotomies by sandwiching the arteriotomy with an intra-arterial toggle and an extraluminal collagen plug. We performed a thorough literature search using various electronic databases. We included studies that reported outcomes after peripheral femorofemoral VA-ECMO decannulation with the Manta vascular closure device. We performed a meta-analysis of proportions on outcome measures, including technical success, bleeding complications, vascular complications, wound complications, major amputation, and procedural-related deaths. We included seven studies with a total of 116 patients. The overall technical success of percutaneous decannulation of VA-ECMO with the Manta vascular closure device was 93.7%. The overall incidence of bleeding, vascular and wound complications was 1.7%, 13.8%, and 3.4%, respectively. No patient required lower limb amputation or died due to VA-ECMO decannulation. Percutaneous decannulation with the Manta vascular closure device is an effective and safe procedure that should be considered in suitable patients on VA-ECMO.